Retrospective Study of Body Weight in Patients with Multiple Myeloma through Different Stages of the Disease - Talamo, G.; Zhu, J.; Dolloff, N. G.; Lamparella, N. E.; Joshi, M.; Barochia, A.; Drabick, J. J.; Malysz, J. (Metabolism and Nutrition in Oncology, 2013)
Little is known regarding body weight changes in patients with multiple myeloma (MM) during the course of their disease, and the influence of obesity in the overall survival (OS) of patients affected by this cancer.We retrospectively collected clinical data from 318 MM patients, and analyzed their weight and body mass index (BMI) at various points throughout the course of the disease, including baseline, pre- and post-peripheral blood stem cell transplant (PBSCT), and time of death.At the time of diagnosis, median BMI was 28.1 (±5.7 SD; range, 15.3–51.8). The majority of MM patients were either overweight or obese, both at the time of initial diagnosis (80%) and in the terminal phase of the disease (66%). Only 5% of patients had malnutrition at the time of death. Median body weight was 81.5 and 79.4 kg before and 6 weeks after high-dose chemotherapy and PBSCT (p<0.001). Kaplan-Meier estimates of OS showed similar results between patients with normal weight and obese patients.The majority of MM patients, at least in our cohort of U.S. residents, are either overweight or obese. Despite the common notion that the terminal phase of cancer is associated with cachexia, most MM patients did not experience a significant and progressive weight loss. PBSCT was associated with a statistically significant but clinically negligible weight loss. Obesity did not seem to influence overall survival in MM.
Keywords: body weight; obesity; overweight; cachexia; multiple myeloma; stem cell transplant